Facilitators' perceptions of problem-based learning and community-based education - Annali E Fichardt; Paula P du Rand (AOSIS, 2000)
In 1997 the School for Nursing, University of the Orange Free State, changed from the traditional lecture method of teaching to problem-based learning and from a curative to a community-based approach. Lecturers from a traditional environment became facilitators and new skills such as listening, dialogue, negotiation, counselling and problemsolving were expected from them. Besides the role change, the environment changed from a structural classroom to an unstructured community. The aim of this research was to determine the perceptions and experiences of facilitators in problem-based learning and community-base education. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.